The everlasting crisis of political representation (TEST Antologia di Diritto Pubblico, 2025)
Vittorio Emanuele Orlando's writing that is commented on here still presents, 130 years later, insights of great interest. Orlando traces the legal foundation of representation in the function of the electoral body to select - and thus elect - the best candidates, understood as the most capable. In this sense, representation appears, at first glance, perfectly homogeneous with the dynamics of the mono-class State of liberal imprint; however, it is Orlando himself who recognises that the role of the emerging political parties is not secondary and that the ideological orientation of the electorate overlaps with, and complements, the choice of the best on the basis of a parameter of ability. If representation does not respond to this function of selecting the most capable, it is destined to enter a crisis without being able to fulfil the premises on which it is founded.
Keywords: Vittorio Emanuele Orlando; Political representation; Electoral capacity; Political parties; Elections